Peningkatan Kemampuan Menulis Puisi Menggunakan Model Pembelajaran Quantum Tipe VAK (Visual, Audiovisual, Kinestetik) - Dian Ramadan Lazuardi; Sri Murti (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2018)
The objective of the research is to improve students' writing poetry skill. There are twenty four third semester students' of Indonesia Language and literature study program of STKIP PGRI Lubuklinggau in this research. The research design was classroom action research. Test was used in data collection. The test was analyzed to know the mean score in pre-action, cycle I, and cycle II. The technique of data analysis was done by sum up the scores from the indicator assessment that obtained by the students. The results showed that learning mastery in writing poetry in pre-action was 45.83% meanwhile in cycle I was 70.83%, and learning mastery improved 91.66% in cycle II. In summary, students' ability in writing poetry improved through type VAK quantun learning. Keywords: Quantum, poetry, writing skill.